Nitrogen fertilization of coffee: organic compost and Crotalaria juncea L. - João Batista Silva Araujo; Mateus Cupertino Rodrigues; Luisa Bastos Rodrigues; Ricardo Henrique Silva Santos; Herminia Emilia Prieto Martinez (Revista Ceres, 2013)
Information concerning the response of coffee to organic fertilizers is scarce. This study evaluates the effect of different doses of compost and Crotalaria juncea L. on growth, production and nitrogen nutrition of coffee trees. The treatments consisted of compost at rates of 25, 50, 75 and 100% of the recommended fertilization, with or without the aerial part of C. juncea. C. juncea was grown with NH4-N (2% 15N) and applied to coffee. The use of C. juncea increased growth in height and diameter of the coffee canopy. In the first year, the percentage of N derived from C. juncea reached 8.5% at seven months and 4.1% at fifteen months after fertilization. In the second year, the percentage of N derived from C. juncea reached 17.9% N at the early harvest, five months after fertilization. Increased rates of compost increased pH , P , K , Ca , Mg , sum of bases , effective CEC, base saturation and organic matter and reduced potential acidity. 15N allowed the identification of the N contribution from C. juncea with percentage of leaf N derived from Crotalaria juncea from 9.2 to 17.9%.